Pendampingan Pembelajaran English Fabulous Learning Mentimeter Berbasis Gamifikasi di SMP Negeri 1 Duhiadaa - Pratiwi Samad; Muliani Muliani; Abdul Yunus Labolo; Muh. Wahyuddin S. Adam; Fairus Suryani Munir; Kurnia Kurnia (I-Com: Indonesian Community Journal, 2024)
Theprogramof gamifies fabulor learning using mentimeter was supporting the students and teachers’ skill and creativity in designing IT-Based learning. The method employed utilizied the fabulous learning with Mentimeter. Based on the outcomes of the initial community empowerment activities, the following conclusions were drawn: 1) participants demonstrated high interest and motivation in learning English and actively participated in English lessons through applications like Mentimeter, Duolingo, Memrise, Quizlet, Quizizz, Kahoot, and Quizwhizzer; 2) participants developed an understanding of using Mentimeter synchronized with gamified English learning to improve students’ vocabulary, speaking, and reading skills; 3) participants successfully applied IT-based English learning applications via Mentimeter, Duolingo, Memrise, Quizlet, Quizizz, Kahoot, and Quizwhizzer; 4) participants grasped the concept of enjoyable learning, which helped increase students’ interest and English language proficiency; and 5) participants were able to develop teaching modules in the form of gamified e-modules.